2003
DOI: 10.2176/nmc.43.364
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Spinal Cord Herniation Associated With Calcified Thoracic Disc Extrusion-Case Report-

Abstract: A 48-year-old man presented with idiopathic spinal cord herniation associated with calcified thoracic disc extrusion at the T7-8 intervertebral level, manifesting as Brown-S áequard syndrome at the thoracic level persisting for 20 years. Preoperative magnetic resonance imaging and computed tomography myelography revealed ventral displacement of the spinal cord and extrusion of a calcified disc at the T7-8 intervertebral level. At surgery, the spinal cord herniation at this level was released from the dura mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
1
14
0
4
Order By: Relevance
“…This pathophysiology is similarly supported by other studies that have suggested calcified disc extrusions may also be the underlying cause of dural rents resulting in ventral transdural cord herniation. 2,10 We have shown that the vast majority (86%) of the fast leaks caused by spiculated osteophytes occur between C-5 and T-7. This distribution is anatomically consistent with the portion of the dura that is most closely opposed and draped over the dorsal surface of the intervertebral discs and vertebral bodies secondary to the normal spinal curvature.…”
Section: Discussionmentioning
confidence: 99%
“…This pathophysiology is similarly supported by other studies that have suggested calcified disc extrusions may also be the underlying cause of dural rents resulting in ventral transdural cord herniation. 2,10 We have shown that the vast majority (86%) of the fast leaks caused by spiculated osteophytes occur between C-5 and T-7. This distribution is anatomically consistent with the portion of the dura that is most closely opposed and draped over the dorsal surface of the intervertebral discs and vertebral bodies secondary to the normal spinal curvature.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial report by Wortzman et al, 1 numerous mechanisms explaining its pathogenesis have been proposed, including minor or unrecognized trauma, 2,3 congenital meningeal malformations, [4][5][6][7][8] CSF flow pulsations, 9,10 and dural erosion by calcified disk remnants. [11][12][13][14][15] While Ͼ100 cases have been reported, no consensus exists as to the most likely mechanism.…”
mentioning
confidence: 99%
“…16 In fact, a review of 65 cases between 1990 and 2010 reported that 15.4% of patients had an asymptomatic presentation. 21 While the etiology of PIIVDC is poorly understood, the natural process of intervertebral disc maturation might provide insight into the increased susceptibility to PIIVDC in 5-to 12-year-old children.…”
Section: Discussionmentioning
confidence: 99%
“…Operative management typically involves discectomy and interbody fusion with or without corpectomy. 4,5,9,22 Medical treatment is more common; 1,3,6,7,16,17 only a handful of reported cases are managed with surgical intervention. 4,5,9,10,12 In our case, the pathology specimen obtained at surgery showed fibrocartilaginous tissue with reactive/regenerative changes consistent with intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%